1981
DOI: 10.1159/000250285
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Benzoyl Peroxide to Decrease Sebaceous Gland Secretion in Acne

Abstract: 10 male patients with inflammatory facial acne were treated for 6 weeks with a 10% benzoyl peroxide gel (PanOxyl®-10) applied to the forehead. There was no significant mean change in sebaceous gland secretion after 4, 5, and 6 weeks of treatment. These findings are at variance with a previously published study which showed that 5% benzoyl peroxide gel inhibited sebaceous gland secretion. Conflicting results from the two studies may be due to differences in patient populations or, more likely, in technical fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 3 publications
0
8
1
Order By: Relevance
“…Discre pancies between the present data and previ ous reports [2,10,13,16] maybe explained by differences in BPO concentrations used and by differences in patient recruitment. But, other explanations may be considered as well.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Discre pancies between the present data and previ ous reports [2,10,13,16] maybe explained by differences in BPO concentrations used and by differences in patient recruitment. But, other explanations may be considered as well.…”
Section: Discussioncontrasting
confidence: 61%
“…BPO was reported to produce a primary irritant dermatitis, and patients did not re port an improvement of seborrhea [1,2], In direct methods of assessing sebum pro duction were found to indicate a sebosuppressive effect of BPO [5,8], More estab lished methods for estimating SER also sug gested that BPO exerted a sebosuppressive effect [6] and clinical observations corrobo rated these observations [4], Other studies failed to show that BPO decreases sebaceous gland secretion in acne [10,13,16]. Recent- ly, 5% BPO was reported to increase SER by 22.5% in acne patients after 1 and 2 months of treatment [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"''3 The site of increased airway resistance in patients with chronic limitation of airflow has been shown to be the small conducting airways,'4 where the obstruction appears to be due to an inflammatory process. [15][16][17][18][19][20] This study examines the nature of the condition in the central airways in patients with chronic bronchitis and determines its relation to the condition in the peripheral airways.…”
Section: Introductionmentioning
confidence: 99%
“…Benzoyl peroxide is considered by most authors as not having sebosuppressive action and some scientific works in fact show an increase in the sebumetric values in subjects treated with this active ingredient 10,17,18 . Other authors report that benzoyl peroxide has neither a positive nor a negative influence on sebaceous secretion whatsoever after topical treatment, attributing the discrepancy in results to the different measuring methods used on the cutaneous lipids and the different conditions when measuring 19 . Lastly, some authors found suppressive action on the sebaceous production 20 …”
Section: Discussionmentioning
confidence: 99%